Formation of foamy macrophages by tuberculous pleural effusions is triggered by the interleukin-10/Signal transducer and activator of transcription 3 axis through ACAT upregulation - Genoula, Melanie (2018)
Fil: Fil: Genoula, Melanie. Academia Nacional de Medicina. Instituto de Medicina Experimental (IMEX-CONICET). Laboratorio de Inmunología de Enfermedades Respiratorias; Argentina.